Effect of ion exchange resins on white and red wine pH: Impact on wine sensory characteristics - Borges, Rita (2019)
The pH control during winemaking is a fundamental parameter by their influence on colour, freshness and to achieve wine microbiological stability. The application of ion exchange resins for wine acidification is based on ability of exchanging ions fixed on functional groups, namely by exchanging cations, such as potassium, with hydrogen ions. Nevertheless, there is an important lack of knowledge on the impact of this operation on wine sensory characteristics. Therefore, the aim of this work was to evaluate the effect of cation exchange resins, on wine pH control and to evaluate their impact on wine sensory quality at industrial scale. In this study a white and a red wine, both from the Douro Valley demarcated region, 2015 vintage, were used. The ion exchange resin treated wine was almost 20% from total white wine volume and almost 30% from total red wine volume. The results obtained in the present study indicated that there were no considerable changes in sensory attributes, although a slight improvement in the aroma and taste, as a result of the ion-exchange pH adjustment. Therefore, the application of ion exchange resins process to wine could be an interesting tool for white and red wine pH adjustment, without interfering with wine sensory quality.